Paediatric asthma prevalence and environmental factors: A community-based cross-sectional study. - Krishna, Dr. Nalla; Paramesh, Pandala; Vislavath, Kavitha; Nunavath, Ravinaik; I Sridhar (Student’s Journal of Health Research Africa, 2025)
Background Pediatric asthma is a critical public health issue with its origins in a complex array of environmental, socio-economic, and potentially genetic factors. Understanding these can aid in crafting targeted preventive measures and management strategies. Aim and Objectives: This study aims to determine the prevalence of pediatric asthma within a representative sample and investigate its associations with environmental conditions, socio-economic status, and familial health history, aiming to unravel the condition’s multifaceted causes. Materials and methods This cross-sectional analysis involved 100 children and adolescents aged 0-18 years. Through interviews and medical record reviews, data were gathered on asthma diagnoses, environmental exposures, socio-economic status, physical activity, and family health history. Chi-square tests and logistic regression analyses identified key asthma predictors. Results The study found a 22% prevalence of asthma, highest among 6-12-year-olds (54.5%), and more common in males (59%). Critical environmental risk factors included poor indoor air quality (affecting 73% of asthmatic children), environmental tobacco smoke exposure (40%), and high outdoor air pollution (50%). Additionally, 68% of affected children came from lower socio-economic backgrounds. The most potent asthma predictor was poor indoor air quality (odds ratio = 4.5), alongside significant influences from tobacco smoke, outdoor pollution, sedentary lifestyles, and family asthma history. Conclusions The study found a prevalence of pediatric asthma at 22%, with the highest burden among school-aged children and males. Environmental and socio-economic factors such as poor indoor air quality, exposure to tobacco smoke, and lower socio-economic status were significantly associated with asthma. These findings underscore the need for targeted interventions to reduce environmental exposures and improve health outcomes in children. Recommendations To reduce pediatric asthma prevalence, prioritize interventions targeting indoor air quality improvement, reduce exposure to tobacco smoke, address outdoor pollution, and promote physical activity, especially in socio-economically disadvantaged areas.